Dual-strategy; complexation-based solid dispersion for enhancing the solubility and dissolution rate of candesartan cilexetil - Latif Abdullah , Saya; Kamal Omer, Huner (Zanco Journal of Medical Sciences (ZJMS), 2026)
Background and objective: Candesartan cilexetil (CC), an angiotensin II receptor blocker indicated for hypertension and heart failure, is classified as a BCS Class II drug which is characterized by low aqueous solubility (0.963 ± 0.062 µg/mL) and limited oral bioavailability (14%–40%). Both factors significantly undermine its therapeutic efficacy and present challenges in formulation development. This study aimed to improve the solubility and dissolution properties of CC through two formulation techniques of solid dispersion with PVPK30 by rotavapor and inclusion complex with HPβCD by kneading. Methods: In this study, solid dispersions and inclusion complexes were formulated at drug to polymer ratios of 1:1, 1:3, and 1:6, with corresponding physical mixtures at a 1:6 ratio. A study on saturated solubility was performed in distilled water. The best formulations—SD3 (solid dispersion with PVP K30) and IC3 (inclusion complex with HPβCD)—were subjected to further characterization. The characterizations consisting of percent drug content, in vitro drug release, Fourier Transform Infrared Spectroscopy, and Powder X-ray Diffraction were performed. Results: SD3 and IC3 improved the solubility of CC by 21.19-fold (20.40 ± 0.139 µg/mL) and 12.22-fold (11.76 ± 0.202 µg/mL), respectively. Both exhibited high drug content—98.47% (SD3) and 98.21% (IC3)—and accomplished over 90% drug release within 15 minutes. FTIR confirmed hydrogen bonding and non-covalent interactions, however PXRD revealed diminished crystallinity and enhanced amorphization. Conclusion: Both PVP K30-based solid dispersion via rotavapor and HPβCD-based inclusion complexation through kneading significantly improved the solubility and dissolution rate of Candesartan cilexetil, with solid dispersion demonstrating superior efficacy for enhancing oral bioavailability.